A Novel Endoscopic Cerenkov Luminescence Imaging System for Intraoperative Surgical Navigation. Issue 8 (1st August 2015) - Song, Tianming; Liu, Xia; Qu, Yawei; Liu, Haixiao; Bao, Chengpeng; Leng, Chengcai; Hu, Zhenhua; Wang, Kun; Tian, Jie
Cerenkov luminescence imaging is an emerging optical technique for imaging the distribution of radiopharmaceuticals in vivo. However, because of the light scattering effect, it cannot obtain optical information from deep internal organs. To overcome this challenge, we established a novel endoscopic Cerenkov luminescence imaging system that used a clinically approved laparoscope and an electron-multiplying charge-coupled device camera. We assessed the performance of the system through a series of in vitro and in vivo experiments. The results demonstrated superior superficial imaging resolution (0.1 mm), a large field of view (500 mm 2 with 10 mm imaging distance), and superb imaging sensitivity (imaging 1 μCi) of our system. It captured the weak Cerenkov signal from internal organs successfully and was applied to intraoperative surgical navigation of tumor resection. It offered objective information of the tumor location and tumor residual during the surgical operation. This technique holds great potential for clinical translation.